Naltrexone Reverses Ethanol Preference and Protein Kinase C Activation in Drosophila melanogaster - Koyyada, Rajeswari; Latchooman, Nilesh; Jonaitis, Julius; Ayoub, Samir S.; Corcoran, Olivia; Casalotti, Stefano O. (Frontiers in Physiology, 2018)
Alcohol use disorder (AUD) is a major health, social and economic problem for which there are few effective treatments. The opiate antagonist naltrexone is currently prescribed clinically with mixed success. We have used naltrexone in an established behavioral assay (CAFE) in Drosophila melanogaster that measures the flies' preference for ethanol-containing food. We have confirmed that Drosophila exposed to ethanol develop a preference toward this drug and we demonstrate that naltrexone, in a dose dependant manner, reverses the ethanol-induced ethanol preference. This effect is not permanent, as preference for alcohol returns after discontinuing naltrexone. Additionally, naltrexone reduced the alcohol-induced increase in protein kinase C activity. These findings are of interest because they confirm that Drosophila is a useful model for studying human responses to addictive drugs. Additionally because of the lack of a closely conserved opiate system in insects, our results could either indicate that a functionally related system does exist in insects or that in insects, and potentially also in mammals, naltrexone binds to alternative sites. Identifying such sites could lead to improved treatment strategies for AUD.